Field notes contributed by Chris Edwards, fall 1997 - Edwards, Chriset al (1997)
Fall report of birds and locations contributed by Chris Edwards. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed